Improving Essay Writing Skills with the Quantum Writer Learning Method in Facing the Destructive Era 4.0 - Fauziah, Syifa Alifia; Gumiandari, Septi (Jurnal Pendidikan Indonesia, 2024)
Learning essay writing skills is considered less interesting and boring for students so that students are less interested in learning essay writing skills. However, using interesting learning methods can be the solution. One of them is by using the quantum writer learning method. This research aims to improve students’ learning of writing skills by using the quantum writer learning method for students. This research was conducted using literature review, by reading various articles, journals, and other publications related to the research topic. Article search is carried out using an accredited online database, namely Google Scholar. In the search for articles, the researcher limited the literature from 2014-2022. The keywords used are "inysa’ writing skills", "quantum writer", "disruptive era 4.0". Based on the search results through Google Scholar using these keywords and after filtering by criteria, out of 20 articles found, only 12 articles are relevant. The results of this study are 1) The quantum writer learning method can be used as an alternative learning method, especially in learning essay writing skills because the two are interconnected. 2) To implement the quantum writer model to improve students’ writing skills, there are stages that must be done by teachers. 3) Quantum writer learning method has a great influence on students’ writing skills. 4) The level of students’ writing ability using the quantum writer method is included in the category of good or quite effective.